Green Nanotechnology—A Road Map to Safer Nanomaterials - Bai, Reenu Geetha (2018)
Nanotechnology has remained at the forefront of scientific research for the past few decades due to its outstanding properties and associated applications. The unlimited potential of nanomaterials have already influenced human life immensely. However, possible harmful impacts of nanomaterials on human health and the environment have always remained a ‘fear factor.’ Extensive research on the toxicity and complexity of nanomaterials has paved the way toward the development of nanotoxicology, which analyzes the root causes of these issues. Nevertheless, the implementation of safer guidelines was needed to ensure that nanomaterials are safe for both human health and the environment. Green chemistry principles were introduced to develop safer methods to produce and handle nanomaterials, leading to the new field of green nanotechnology. This chapter discusses the principles, biomedical applications, limitations, and future prospects of green nanotechnology.